Atrial Fibrillation Exacerbates Cognitive Dysfunction and Cerebral Perfusion in Heart Failure - Alosco, Michael L. (Pacing Clin Electrophysiol, 2014)
BACKGROUND: Heart failure (HF) increases risk for cognitive impairment in part due to the negative effects of cardiac dysfunction on cerebral perfusion. Atrial fibrillation (AF), an independent risk factor for cognitive impairment, often accompanies HF and is associated with lower systemic perfusion. However, no study has examined the associations among AF, cognitive function, and cerebral perfusion in patients with HF. METHODS: 187 HF patients completed neuropsychological testing and underwent transcranial Doppler ultrasonography. Cerebral blood flow velocity of the middle cerebral artery (CBF-V) operationalized cerebral perfusion. A medical chart review ascertained AF. RESULTS: 32.1% of HF patients had a history of AF. HF patients with AF exhibited worse global cognition, memory, and CBF-V relative to patients without AF. These effects remained after HF severity and other demographic and medical factors were taken into account. Partial correlations controlling for possible confounds showed decreased CBF-V predicted worse cognition in multiple domains in the overall sample (r = 0.13 to 0.15, p < 0.05) and in the subgroup of HF patients with AF (r = 0.26 to r = 0.28, p < 0.05), but not among HF patients without AF. CONCLUSIONS: AF exacerbates cognitive deficits in HF possibly through its association with decreased cerebral perfusion. Longitudinal studies are needed to determine whether AF accelerates cognitive decline in HF and whether medical (e.g., ablation) and lifestyle interventions (e.g., exercise programs) that target cerebral perfusion improve cognitive outcomes in patients with HF and AF.